Problems in the Management of Islamic Religious Education in Schools and Universities - Purwanto, Agus (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This study aims to address issues in the management of Islamic Religious Education (PAI) in both general schools and higher education institutions. The research employs a library research method with a descriptive-analytical approach to collect and analyze data from written sources such as journals, books, and online materials. The analysis is conducted conceptually and qualitatively using content analysis techniques to integrate relevant perspectives and provide an in-depth explanation of the research phenomenon. Islamic Religious Education in general schools faces challenges such as limited time allocation, traditional teaching approaches, and insufficient attention to affective and psychomotor aspects. External factors, such as an unsupportive environment, low parental awareness, and the influence of technology, further hinder learning effectiveness. Solutions include enhancing teacher competence, innovating teaching methods, integrating Islamic technology, and fostering synergy between schools, parents, and communities. In higher education, challenges include limited credit hours, lack of curriculum continuity, and inadequate lecturer competence, requiring holistic approaches and specific regulations for integrating religious values.